Reference Values and Psychometric Properties of the Quality of Life After Traumatic Brain Injury-Overall Scale in Italy, The Netherlands, and the United Kingdom - Wu, Yi-Jhen; Rauen, Katrin; Zeldovich, Marina; Voormolen, Daphne C.; Covic, Amra; Cunitz, Katrin; Plass, Anne-Marie; Polinder, Suzanne; Haagsma, Juanita A.; von Steinbuechel, Nicole (Value in health, 2021)
The Quality of Life after Brain Injury-Overall Scale (QOLIBRI-OS) is a short screening instrument for assessing disease-specific health-related quality of life (HRQoL) after traumatic brain injury. To date, no reference values are available for the QOLIBRI-OS in general populations. Thus, this study aimed to establish reference values for the QOLIBRI-OS in general population samples from Italy, The Netherlands, and the United Kingdom. Data were collected using an online survey. The total sample comprised 11759 participants, consisting of 3549 Italian, 3564 Dutch, and 4646 British subjects. In this sample, 49% of the total sample did not report any health complaints, whereas 51% had at least 1 chronic health condition. Reference values were deduced for the QOLIBRI-OS for health-condition–related samples and total general population samples per country. To ensure the comparability of these values, measurement invariance was assessed using a multigroup confirmatory factor analysis. Covariates characterizing the reference values were selected with the help of regression analyses. The confirmatory factor analysis confirmed that the QOLIBRI-OS scores measured the same traumatic brain injury–specific HRQoL construct across the 3 countries. Healthy individuals reported significantly higher HRQoL than individuals with at least 1 chronic health condition. Older age and higher education levels were significantly associated with higher HRQoL. Because the reference values displayed differences in terms of age and education level across the 3 countries, we recommend using country-specific reference values stratified by sociodemographic and health status in research and clinical practice. •The cut-off value of the Quality of Life after Traumatic Brain Injury Overall-Scale (QOLIBRI-OS) has derived from existing reference values of the mental component summary of the SF36 in general U.S. populations in TBI research.•This paper contributes to existing knowledge by providing sex-, age-, education- related reference values for the QOLIBRI-OS in three European general population samples (ie, Italy, the Netherlands, and the United Kingdom) and examining the quality of translations of the QOLIBRI-OS in these 3 countries.•The reference values are available to researchers and clinicians to reliably compare the disease-specific HRQoL of individuals after TBI in national and international contexts.